A preparation method of high adsorption capacity adsorbent and adsorbent
Through carbonization activation, pickling and hot alkali treatment, high adsorption activated carbon materials were prepared, which solved the shortcomings of existing carbon-based adsorption materials in terms of CO2 adsorption and selectivity, and achieved efficient carbon capture and VOC waste gas treatment.
Patent Information
- Application Number
- CN202310170417.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The existing carbon-based adsorption materials have shortcomings in CO2 adsorption amount and selectivity, which is difficult to meet the application needs of large-scale low CO2 concentration flue gas carbon capture technology.
By using coal and related products of coal as carbon sources, and using carbon activation, pickling and hot alkali treatment and other processes, activated carbon materials with large specific surface area and high microporosity are prepared to improve their adsorption activity.
The prepared adsorbent has high adsorption amount, fast adsorption rate and excellent cycle stability. It is suitable for carbon capture and VOC waste gas treatment and is suitable for large-scale production and application.
Smart Images

Figure CN118437274B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of dry absorbent preparation, and particularly relates to a preparation method of an absorbent with high adsorption capacity and the absorbent. Background Art
[0002] Adsorption carbon capture technology is considered to be the second-generation capture technology with the most development potential because of its large potential for energy consumption and comprehensive cost reduction, environmental friendliness, and low equipment corrosion. Developing low-cost, high-adsorption CO2 adsorption materials is the key to reducing the energy consumption and cost of adsorption carbon capture technology.
[0003] Chinese patent application CN110465268A discloses a method for preparing a carbon-based CO2 adsorbent. The carrier of the carbon-based CO2 adsorbent prepared by the invention needs to have certain pore requirements, wherein the surface structure of the semi-coke activated by water vapor should be mainly mesopores and macropores, with the advantages of rich pore structure, high strength, strong regeneration, low cost, etc. The acidic groups and alkaline metal components in the semi-coke can be removed by acid washing to ensure a good organic amine loading effect. The organic amine is alkaline and loaded on the mesoporous structure, thereby improving its adsorption effect on acidic gases. First, semi-coke is obtained by pyrolysis of lignite, and water vapor is introduced to improve the surface structure of the semi-coke to obtain a developed pore structure, which can effectively increase the loading amount of the additive; then, ultrasonic impregnation treatment is performed by HF and HCl solution to remove alkali metals, ash, SiO2 and other substances that are not conducive to adsorption on the surface of the semi-coke; finally, the carbon-based CO2 adsorbent is obtained by loading the organic amine. The adsorbent has the characteristics of strong adsorption capacity, strong stability and low cost, and can efficiently capture CO2. The preparation method of the adsorbent in the invention is relatively complicated, and organic amines are used for modification. Organic amines have poor stability and are expensive, and are not suitable for large-scale production.
[0004] Chinese patent CN113428854B discloses a method for preparing a wood-based porous carbon material for CO2 adsorption. The invention uses waste eucalyptus wood powder as raw material, adopts a strategy of regulating with a trace activator KOH, and synthesizes a wood-based porous carbon material with controllable porosity, high specific surface area and high pore volume through a fixed-point one-step activation method. Using waste biomass as a carbon source has the obvious advantages of low cost and sustainable regeneration. The fixed-point one-step activation strategy has simple steps and low equipment requirements, which also reduces production costs on the other hand. Compared with the traditional activation method, the wood-based porous carbon material is prepared by a one-step fixed-point activation strategy, and the amount of KOH activator used is only 1 / 6 to 1 / 10 of the amount of the traditional activator. The pore structure and distribution of the wood-based carbon material can be regulated by a trace activator to achieve the directional preparation of CO2 gas adsorption materials. The porous carbon material has a main peak pore size that is suitable for the kinetic size of CO2, so that when the material is used for CO2 adsorption, it exhibits 5.21mmol g -1(0 °C, 1 atm) and 3.54 mmol g -1 (25°C, 1atm) has excellent CO2 adsorption capacity and excellent cycle reversibility. However, this method uses a large amount of organic solvents and reagents, and the CO2 adsorption capacity of the material is still low, which is not suitable for the application of large-scale carbon capture technology.
[0005] Carbon-based adsorption materials are very suitable for large-scale carbon capture due to their large specific surface area, developed pore structure, low price, simple preparation and good stability. However, there have always been fatal problems such as low CO2 adsorption capacity and poor selectivity, which makes it difficult to meet the application requirements of large-scale low CO2 concentration flue gas carbon capture technology. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing an adsorbent with high adsorption capacity. The adsorbent prepared by this method has a large specific surface area, high microporosity, high adsorption capacity, fast adsorption rate, and excellent cycle stability, and is suitable for fields such as carbon capture and VOC waste gas treatment.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing an adsorbent with high adsorption capacity, comprising the following steps:
[0009] 1) mixing and grinding a base material and an activator to obtain a mixed material; the base material is selected from one or more of coal and coal-related products;
[0010] 2) carbonizing and activating the obtained mixed material in a protective gas to obtain an activated material;
[0011] 3) washing the activated material in an acid solution, then washing with an aqueous solution, and drying to obtain an activated carbon material;
[0012] 4) treating the obtained activated carbon material with alkali to obtain an alkali-treated activated carbon material;
[0013] 5) The activated carbon material after alkali treatment is washed with water and dried to obtain the adsorbent.
[0014] Further, the coal related products are coal liquefaction residue or coal tar pitch.
[0015] Furthermore, in step 1), an activation aid is also added; the activator is potassium hydroxide and / or sodium hydroxide; the activation aid is one or more of potassium nitrate, potassium carbonate, sodium carbonate and zinc chloride.
[0016] Furthermore, the mass ratio of the base material to the activator and the activation aid is 1:(0.5-4):(0-1). The activator plays a leading role in the activation process. Adding too little activator will lead to incomplete activation of the material, underdeveloped pore structure, and poor adsorption effect; while adding too much activator will cause the material to be over-activated, thereby causing the collapse and destruction of the pore structure, and then forming larger mesopores or macropores, resulting in a decrease in the adsorption performance of the material. Generally, the more suitable addition amount is between 0.5-4 times the base material; the activation aid mainly plays an auxiliary activation role. The addition of the activation aid will further enhance the activation effect of the material, making the pore structure of the material more developed. The activation aid and the activator work together to further enhance the activation effect of the activator. However, relative to the activator, its addition amount should usually be less than the addition amount of the activator. Generally, the more suitable addition amount is 0-1 times the mass of the base material. Preferably, the addition amount of the activation aid is 5%-50% of the mass of the base material. It should be noted that although activation agents can further improve material properties, some activation agents are hazardous chemicals. If the complexity, safety and cost control of the scale-up process are taken into consideration, the benefits of the improved activation effect are negligible compared to their harmfulness, so you can choose not to add them.
[0017] Furthermore, before step 1), the base material is screened and impurities are removed, and particles of 100-150 μm are screened out as the base material used in step 1); smaller base material particles are more conducive to obtaining a larger adsorbent specific surface area, higher microporosity, and higher adsorption capacity, but it is difficult to achieve if the particles are too small, which will result in excessively high costs. Therefore, the present invention screens out particles with a particle size of 100-150 μm as the base material.
[0018] Preferably, in step 1), a mixed material having a particle size of 10-50 μm is obtained by grinding.
[0019] Further, in step 2), the protective gas is nitrogen or argon; the temperature is raised to 200-400°C at a heating rate of 1-10°C / min, and the temperature is maintained constant for 0.5-3 hours for pyrolysis and preliminary carbonization, and then the temperature is raised to 550-700°C at a heating rate of 1-10°C / min, and the temperature is maintained constant for 0.5-5 hours for deep carbonization activation. Maintaining a constant temperature of 200-400°C for 0.5-3 hours is mainly a process of pyrolysis and preliminary carbonization of the mixed material, removing impurities such as volatiles, so that atoms such as hydrogen and oxygen are continuously reduced, and carbon is continuously enriched; maintaining a constant temperature of 550-700°C for 0.5-5 hours is mainly a process of deep carbonization activation, in which a series of cross-linking or polycondensation reactions occur between the activator and the carbon material, and the carbon atoms are continuously cyclized and aromatized, thereby forming a carbon material with a certain pore structure.
[0020] Furthermore, in step 3), the acid solution is one or more of hydrochloric acid, sulfuric acid, and phosphoric acid with a mass fraction of 0.1-10wt%. The acid washing is mainly to remove mineral impurities such as potassium and sodium remaining after the carbonization activation reaction, thereby increasing the specific surface area of the material and improving the adsorption performance of the material.
[0021] Further, in step 4), the temperature of the alkali treatment is 50-200°C, and the time of the alkali treatment is 0.5-6 hours. The alkaline solution used for the alkali treatment is a potassium hydroxide or sodium hydroxide aqueous solution with a concentration of 1-5 mol / L. During the alkali treatment, if the concentration of the alkali solution used is too high, it will be highly corrosive, affecting the long-term stability of the equipment and greatly increasing the difficulty of post-treatment of the reaction product. If the concentration of the alkali solution used is too low, it will affect the effect of the alkali treatment. The hot alkali process can further remove impurities such as ash in the material, and on the basis of not changing the pore structure of the activated carbon material, it increases the surface polarity of the material and greatly improves the adsorption performance of the material.
[0022] The second aspect of the present invention provides an adsorbent with high adsorption capacity obtained by the above preparation method.
[0023] The technical solution provided by the present invention has the following beneficial effects:
[0024] The present invention uses coal and coal-related products as carbon sources, and prepares activated carbon materials with large specific surface area and high microporosity through processes such as carbonization activation and acid washing. The adsorption activity of the carbon material is further improved through a hot alkali treatment process, effectively increasing the adsorption capacity of the material. The adsorption material prepared by this method has the advantages of large micropore specific surface area, high adsorption capacity, fast adsorption rate, good cycle stability, etc., and the preparation process is simple and the cost is low. It is suitable for fields such as carbon capture and VOC waste gas treatment, and is very suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A process roadmap for the preparation of adsorbents with high adsorption capacity.
[0026] Figure 2 This is a performance diagram of the adsorption-desorption cycle of the adsorbent in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described below by means of specific embodiments. The embodiments of the present invention are only used as illustrations of the present invention and do not mean that the scope of the present invention is limited thereto.
[0028] The raw materials and testing methods used in the examples or comparative examples are introduced below:
[0029] Raw materials used:
[0030] The coal liquefaction residue came from the Ordos Coal-to-Liquid Branch of China Shenhua Coal-to-Liquid Chemical Co., Ltd.;
[0031] Xinjiang coal was purchased from an activated carbon plant in Xinjiang;
[0032] Potassium hydroxide was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0033] Potassium nitrate was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0034] Hydrochloric acid was purchased from Beijing Tongguang Fine Chemical Company;
[0035] Zinc chloride was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0036] Test methods used:
[0037] Specific surface area of adsorbent: N2 physical adsorption (77K) was measured using a Micromeritics ASAP 2460 gas adsorption instrument produced by Micromeritics Instruments, Inc., USA. The sample was degassed at 300°C for 4 hours. According to the recommendations of IUPAC, the surface area was calculated using the Brunauer-Emmett-Teller (BET) method in the relative pressure range of P / P0 = 0.015-0.3;
[0038] Microporosity: micropore specific surface area of adsorbent / specific surface area of adsorbent;
[0039] Adsorption capacity: The adsorption capacity of the samples was measured using a STA449 F3 synchronous thermal analyzer produced by NETZSCH, Germany. The test conditions were as follows: the samples were pretreated at 300°C in N2 for 30 minutes to remove any physically adsorbed impurities such as H2O and / or CO2. After the temperature was cooled and stabilized at 40°C, the adsorption gas was switched to calculate the adsorption capacity by weight gain.
[0040] Adsorption isotherm: BSD-PM analyzer was used to measure the adsorption isotherms of different gases at different temperatures. The sample degassing temperature was 200 °C and the degassing time was 300 min.
[0041] Carbon tetrachloride adsorption rate (static): measured in accordance with GB / T 26900-2011.
[0042] Example 1
[0043] The coal liquefaction residue is screened and impurities are removed, and particles of 100 μm are obtained after screening; the coal liquefaction residue after screening and impurities removal, sodium hydroxide and potassium carbonate are ground and mixed uniformly in a mass ratio of 1:1:1 to obtain a mixed material of 10 μm.
[0044] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 650°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material.
[0045] The activated material is washed in a 5wt% dilute hydrochloric acid solution until no bubbles emerge, then washed with an aqueous solution until neutral, and then dried to obtain an activated carbon material.
[0046] The activated carbon material was treated in a 2 mol / L potassium hydroxide solution at 100°C for 3 hours to obtain an alkali-treated activated carbon material, which was then washed with water and dried to obtain an adsorbent with a high adsorption capacity.
[0047] The specific surface area of the prepared adsorbent is 1673m 2 / g, and the microporosity is as high as 99.6%. Figure 2 It mainly reflects the CO2 adsorption capacity of the adsorbent and the adsorption-desorption cycle stability. The first CO2 adsorption was carried out after pretreatment at 300°C under nitrogen conditions. At 40°C, the CO2 adsorption capacity was tested under 15% CO2 + 85% N2 simulated flue atmosphere, and the CO2 adsorption capacity was about 8.7wt%. The CO2 adsorption capacity at 0°C and 1 bar can be as high as 37.3wt%. The 2nd to 51st adsorption-desorption cycle tests were conducted at 120°C, nitrogen conditions, and then desorbed, and then tested at 40°C, 15% CO2 + 85% N2 simulated flue gas. The measured CO2 adsorption capacity is called the working adsorption capacity. It can be seen that the CO2 working adsorption capacity is basically maintained at about 7%, which is very stable. The CO2 working adsorption capacity retention rate of 50 cycles is above 98%, and the adsorption equilibrium can be reached in a short time. The adsorption rate is fast and the cycle stability is good.
[0048] In addition, the high adsorption capacity adsorbent prepared in Example 1 was used to adsorb other gases, and the measured carbon tetrachloride adsorption rate (static) reached 212%. At 40°C, the adsorption amounts of ethylene and methane were 11.7% and 4.5%, respectively. The adsorption performance was much better than that of the adsorbent produced by a Xinjiang activated carbon manufacturer in Comparative Example 1.
[0049] Example 2
[0050] The Xinjiang coal is screened and impurities are removed, and particles of 110 μm are obtained after screening; the Xinjiang coal after screening and impurities removal, potassium hydroxide and potassium nitrate are ground and evenly mixed in a mass ratio of 1:1:1 to obtain a mixed material of 15 μm.
[0051] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 650°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material.
[0052] The activated material is washed in a 5wt% dilute hydrochloric acid solution until no bubbles emerge, then washed with an aqueous solution until neutral, and then dried to obtain an activated carbon material.
[0053] The activated carbon material was treated in a 1 mol / L potassium hydroxide solution at 100°C for 3 hours to obtain an alkali-treated activated carbon material. The alkali-treated activated carbon material was washed with water and dried to obtain an adsorbent with a high adsorption capacity.
[0054] The specific surface area of the prepared adsorbent is 1528m 2 / g, the microporosity is as high as 99.1%. At 40℃, the CO2 adsorption capacity under 15%CO2+85%N2 simulated flue atmosphere is about 7.6wt%, and the CO2 adsorption capacity under 0℃ and 1bar conditions can be as high as 34.6wt%. There is no attenuation in the CO2 adsorption capacity after 10 adsorption and desorption cycles, and the adsorption equilibrium can be reached in a short time. The adsorption rate is fast and the cycle stability is good.
[0055] Example 3
[0056] The coal liquefaction residue is screened and impurities are removed, and particles of 125 μm are obtained after screening; the coal liquefaction residue after screening and impurities removal and potassium hydroxide are ground and mixed in a mass ratio of 1:0.85 to obtain a mixed material of 30 μm.
[0057] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 10°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 650°C at a heating rate of 10°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material.
[0058] The activated material is washed in a 5wt% dilute hydrochloric acid solution until no bubbles emerge, then washed with an aqueous solution until neutral, and then dried to obtain an activated carbon material.
[0059] The activated carbon material was treated in a 3 mol / L potassium hydroxide solution at 100°C for 3 hours to obtain an alkali-treated activated carbon material. The alkali-treated activated carbon material was washed with water and dried to obtain an adsorbent with a high adsorption capacity.
[0060] The specific surface area of the prepared adsorbent is 1356m 2 / g, the microporosity is as high as 88.9%. At 40℃, the CO2 adsorption capacity in the simulated flue atmosphere of 15% CO2+85% N2 is about 5.8wt%, and the CO2 adsorption capacity at 0℃ and 1bar can be as high as 27.2wt%.
[0061] Example 4
[0062] The coal liquefaction residue is screened and impurities are removed, and particles of 135 μm are obtained after screening; the coal liquefaction residue after screening and impurities removal and potassium hydroxide are ground and mixed in a mass ratio of 1:2 to obtain a mixed material of 40 μm.
[0063] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 600°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material.
[0064] The activated material is washed in a 5wt% dilute hydrochloric acid solution until no bubbles emerge, then washed with an aqueous solution until neutral, and then dried to obtain an activated carbon material.
[0065] The activated carbon material was treated in a 2 mol / L potassium hydroxide solution at 100°C for 3 hours to obtain an alkali-treated activated carbon material, which was then washed with water and dried to obtain an adsorbent with a high adsorption capacity.
[0066] The specific surface area of the prepared adsorbent is 1308m 2 / g, the microporosity is as high as 92.5%. At 40℃, the CO2 adsorption capacity in the simulated flue atmosphere of 15% CO2+85% N2 is about 6.6wt%, and the CO2 adsorption capacity at 0℃ and 1bar can be as high as 28.4wt%.
[0067] Example 5
[0068] The coal liquefaction residue is screened and impurities are removed, and particles of 150 μm are obtained after screening; the coal liquefaction residue after screening and impurities removal, potassium hydroxide, and zinc chloride are ground and mixed uniformly in a mass ratio of 1:1:0.1 to obtain a mixed material of 50 μm.
[0069] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 650°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material.
[0070] The activated material is washed in a 5wt% dilute hydrochloric acid solution until no bubbles emerge, then washed with an aqueous solution until neutral, and then dried to obtain an activated carbon material.
[0071] The activated carbon material was treated in a 2 mol / L potassium hydroxide solution at 100°C for 3 hours to obtain an alkali-treated activated carbon material, which was then washed with water and dried to obtain an adsorbent with a high adsorption capacity.
[0072] The specific surface area of the prepared adsorbent is 1490m 2 / g, the microporosity is as high as 93.8%. At 40℃, the CO2 adsorption capacity in the simulated flue atmosphere of 15% CO2+85% N2 is about 6.9wt%, and the CO2 adsorption capacity at 0℃ and 1bar can be as high as 30.9wt%.
[0073] Comparative Example 1
[0074] The activated carbon produced by a Xinjiang activated carbon manufacturer has a specific surface area of about 1267m 2 / g, the microporosity is 86.6%. At 40°C, the CO2 adsorption capacity in the simulated flue atmosphere of 15% CO2 + 85% N2 is only 1.8wt%.
[0075] In addition, the adsorbent prepared in Comparative Example 1 was used to adsorb other gases, and the measured carbon tetrachloride adsorption rate (static) was 104%. At 40° C., the adsorption amounts of ethylene and methane were 8.8% and 1.5%, respectively.
[0076] Comparative Example 2
[0077] The coal liquefaction residue is screened and impurities are removed, and particles of 100 μm are obtained after screening; the coal liquefaction residue after screening and impurities removal, sodium hydroxide and potassium carbonate are ground and mixed uniformly in a mass ratio of 1:1:1 to obtain a mixed material of 10 μm.
[0078] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 650°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material.
[0079] The activated material is washed in a 5 wt % dilute hydrochloric acid solution until no bubbles emerge, then washed with an aqueous solution until neutral, and then dried to obtain an activated carbon material as an adsorbent.
[0080] The prepared adsorbent was not subjected to thermal alkali treatment and had a specific surface area of 1673 m 2 / g, the microporosity is as high as 99.6%, but at 40℃, the CO2 adsorption capacity in the simulated flue atmosphere of 15%CO2+85%N2 is only 3.5wt%.
[0081] Comparative Example 3
[0082] The coal liquefaction residue is screened and impurities are removed, and particles of 100 μm are obtained after screening; the coal liquefaction residue after screening and impurities removal, sodium hydroxide and potassium carbonate are ground and mixed uniformly in a mass ratio of 1:1:1 to obtain a mixed material of 10 μm.
[0083] The mixed material was placed in a nitrogen atmosphere, and the temperature was increased from room temperature to 300°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for pyrolysis and preliminary carbonization. The temperature was then increased to 650°C at a heating rate of 5°C / min, and kept constant at that temperature for 1 hour for deep carbonization activation to obtain the activated material as an adsorbent.
[0084] The prepared adsorbent was not subjected to acid washing or hot alkali treatment, and its specific surface area was only 972 m 2 / g, the microporosity is only 64.7%. At 40℃, the CO2 adsorption capacity in the simulated flue atmosphere of 15%CO2+85%N2 is only 2.6wt%.
[0085] Through the test, it can be seen that the preparation method of the high adsorption capacity adsorbent proposed in this application is simple and low-cost, and the prepared adsorption material has a large specific surface area, which can reach 1356-1673m 2 / g, microporosity up to 88.9%-99.6%, high adsorption capacity, fast adsorption rate, and excellent cycle stability, suitable for the adsorption of different gases and can achieve good adsorption effects. The CO2 adsorption capacity under 40℃, 15%CO2+85%N2 simulated flue atmosphere is as high as 5.8-8.7wt%, and the CO2 adsorption capacity under 0℃, 1bar conditions can be as high as 27.2-37.3wt%, and the adsorption performance is far better than commercially available activated carbon materials.
[0086] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. Application of a high adsorption capacity adsorbent in carbon dioxide adsorption, characterized in that: The preparation method of the high adsorption capacity adsorbent comprises the following steps: 1) Mixing and grinding a base material and an activator to obtain a mixed material; the base material is selected from one or more of coal and coal-related products; the mass ratio of the base material to the activator is 1:(0.5-4); 2) The obtained mixed material is carbonized and activated in a protective gas to obtain an activated material; the carbonization activation is carried out by heating the mixture to 200-400°C at a heating rate of 1-10°C / min, maintaining the constant temperature for 0.5-3 hours for pyrolysis and preliminary carbonization, and then heating the mixture to 550-700°C at a heating rate of 1-10°C / min, maintaining the constant temperature for 0.5-5 hours for deep carbonization activation; 3) washing the activated material in an acid solution, then washing with an aqueous solution, and drying to obtain an activated carbon material; 4) treating the obtained activated carbon material with alkali to obtain an alkali-treated activated carbon material; the alkali treatment temperature is 100-200° C., the alkali treatment time is 0.5-6 hours, and the alkali solution used for the alkali treatment is a potassium hydroxide or sodium hydroxide aqueous solution with a concentration of 1-5 mol / L; 5) washing and drying the activated carbon material after the alkali treatment to obtain the adsorbent; Activated carbon treated with hot alkali can increase the surface polarity of the material without changing the pore structure of the activated carbon material.
2. The use according to claim 1, characterized in that: The coal-related products are coal liquefaction residue or coal tar pitch.
3. The use according to claim 1, characterized in that: In step 1), an activation aid is also added; The activator is potassium hydroxide and / or sodium hydroxide; The activation aid is one or more of potassium nitrate, potassium carbonate, sodium carbonate and zinc chloride.
4. The use according to claim 3, characterized in that: The mass ratio of the base material to the activator and the activation aid is 1:(0.5-4):(0-1).
5. The use according to any one of claims 1 to 4, characterized in that: Before step 1), the base material is screened to remove impurities, and particles of 100-150 μm are screened out as the base material used in step 1).
6. The use according to claim 5, characterized in that: In step 1), a mixed material with a particle size of 10-50 μm is obtained through the grinding.
7. The use according to any one of claims 1 to 4, characterized in that: In step 2), the protective gas is nitrogen or argon.
8. The use according to any one of claims 1 to 4, characterized in that: In step 3), the acid solution is one or more of hydrochloric acid, sulfuric acid, and phosphoric acid with a mass fraction of 0.1-10 wt%.
Citation Information
Patent Citations
Preparation method and applications of carbon based CO2 adsorbent
CN110465268A
A lignocellulosic porous carbon material for CO2 adsorption and its preparation method
CN113428854B
Process for preparing high-specific surface area composite pore structure coal-based activated carbon by using low dosage of KOH
CN102674346A